ARE THE ORGANIZATIONAL COMMITMENT AND WORK ENGAGEMENT OF GENERATION Y AND Z IMPORTANT FOR IMPROVING THEIR PERFORMANCE IN STATE-OWNED COMPANIES: A STUDY FROM INDONESIA (British Journal of Global Ecology and Sustainable Development, 2023)
This study aims to investigate how organizational commitment and work engagement predict the performance of Generations Y and Z in state-owned companies and examine the mediating role of work engagement in the influence of organizational commitment on their performance